Effect of NaOH concentration on sorption isotherm of carboxymethyl rice starch films and prediction models - Pornchai Rachtanapun (2018)
Effect of NaOH concentration on the sorption isotherm of carboxymethyl rice starch (CMSr) films was investigated. Sorption isotherms are important for predicting moisture sorption properties of the films via moisture sorption empirical models. The moisture sorptions isotherm of CMSr films synthesized with different NaOH concentrations (0, 10, 20, 30, 40 and 50% w/v) were studied at various relative humidity (16, 35, 55 and 76% RH), at 25±1°C. The equilibrium moisture content of the films increased dramatically above aw= 0.6. Guggenheim-Anderson-de Boer (GAB), Brunauer-Emmett-Teller (BET) and Oswin sorption models were fitted to the experimental data. The results showed that the increase in NaOH concentration caused a decrease in the monolayer water content (M0) of the films. The GAB model was found to be the best-fit model for CMSr films at aw0.1-0.76, 25±1°C.